2009
DOI: 10.1111/j.1439-0469.1987.tb00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Antennal sensory structures in Nepticulidae (Lepidoptera) and their phylogenetic implications

Abstract: Antennae of representatives of most genera and subgenera of Nepticulidae have been examined in detail with SEM. Flagellar segments are highly uniform and possess each 1–3 s. trichodea, 1–3 long s. chaetica type I, 12 short s. chaetica type II and 0–2 s. coeloconica of a simpified type without “picket fence”. The dominating structure is a pair of s. vesiculoclada, a unique sensillum type, believed to be a synapomorphy for the Nepticulidae. A pair is present on alt flagellomeres in male antennae but not on all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…These subtype sensilla observed in the two species of this study were similar to those found in C. cactorum (Lepidoptera: Pyralidae), T. batesi (Lepidoptera: Tortricidae), and C. medinalis (Lepidoptera: Pyralidae) (Gómez and Carrasco, ; Pophof et al, ; Sun et al, ). Sensilla coeloconica subtype II without circular fence has been described in a few moths, which are always present in small numbers (Faucheux, ; Van Nieukerken and Dop, ; Wall, ). In antenna of Agathiphaga vitiensis (Lepidoptera: Agathiphagidae) and A. queenslandensis (Lepidoptera: Agathiphagidae), three morphological types of s. coeloconica were described (Faucheux, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These subtype sensilla observed in the two species of this study were similar to those found in C. cactorum (Lepidoptera: Pyralidae), T. batesi (Lepidoptera: Tortricidae), and C. medinalis (Lepidoptera: Pyralidae) (Gómez and Carrasco, ; Pophof et al, ; Sun et al, ). Sensilla coeloconica subtype II without circular fence has been described in a few moths, which are always present in small numbers (Faucheux, ; Van Nieukerken and Dop, ; Wall, ). In antenna of Agathiphaga vitiensis (Lepidoptera: Agathiphagidae) and A. queenslandensis (Lepidoptera: Agathiphagidae), three morphological types of s. coeloconica were described (Faucheux, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the department was short lived being closed down after budget cuts in 1985, cuts that were particularly detrimental to taxonomy. EvN finished his degree in 1986 after the group had been disbanded (van Nieukerken 1983b; 1985b; 1986b; van Nieukerken and Dop 1987). His thesis built upon Scoble’s results, but mainly based on the Holarctic fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Together with his MSc student, Henk Dop, he also extensively studied antennal ultrastructure. Van Nieukerken and Dop discovered a novel sensillum, which they named sensillum vesiculocladum (van Nieukerken and Dop 1987). The work led to a first checklist of the Western Palearctic species (van Nieukerken 1986a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the unique sensillum vesiculocladum has been identified. This type is lacking in the females of some species (Nieukerken & Dop 1987). The male antenna possesses more flagellomeres than the females.…”
Section: Nepticuloidea Nepticulidaementioning
confidence: 96%
“…Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/21/15 6:02 PM Sensillum vesiculocladum is a specialized sensillar type present in Nepticulidae (Nieukerken & Dop 1987). The indivual sensilla are usually covering large areas of the antennal surface, but do not extend far from the antennal surface.…”
Section: Definition Of Antennal Sensillar Typesmentioning
confidence: 99%